Risk factors for the development and evolution of deep tissue injuries: A systematic review. Issue 3 (August 2022) - Wynn, Matthew; Stephens, Melanie; Pradeep, Sheba; Kennedy, Robert
Abstract: Aims: The aim of this systematic review is to identify the current epidemiological evidence indicating the unique risk factors for deep tissue injury (DTI) compared to grade I-IV pressure injury (PI), the proportion of DTI which evolve rather than resolve and the anatomical distribution of DTI. Methods: A systematic literature search was undertaken using the MEDLINE and CINAHL Plus databases using the search terms 'Deep tissue injury OR DTI [Title/abstract]'. A google scholar search was also conducted in addition to hand searches of relevant journals, websites and books which were identified from reference lists in retrieved articles. Only peer-reviewed English language articles published 2009–2021 were included, with full text available online. Results: The final qualitative analysis included nine articles. These included n = 4 retrospective studies, n = 4 prospective studies and n = 1 animal study. Conclusion: The literature indicates that the majority of DTI occur at the heel and sacrum although in paediatric patients they are mainly associated with medical devices. Most DTI are reported to resolve, with between 9.3 and 27% deteriorating to full thickness tissue loss. Risk factors unique to DTI appear to include anaemia, vasopressor use, haemodialysis and nicotine use although it is unclear if these factors are unique to DTI or are shared with grade I-IV PI. Factors associated with deterioration include cooler skin measured using infrared thermography and negative capillary refill. With 100% of DTI showing positive capillary refill in one study resolving without tissue loss (p = 0.02) suggesting this may be an effective prognostic indicator. More prospective studies are required focusing on establishing causal links between risk factors identified in earlier retrospective studies. Ideally these should use statistically powered samples and sufficient follow up periods allowing DTI outcomes to be reached. Further work is also needed to establish reliable diagnostic criteria for DTI in addition to more studies in the paediatric population. Highlights: Most DTI occur at the heel and sacrum although in paediatric patients they are mainly associated with medical devices. Only 9.3–27% of DTI deteriorate to full thickness tissues loss although this may be an underestimate. Risk factors for DTI development appear to include anaemia, vasopressor use, haemodialysis and nicotine use. Risk factors for DTI evolution appear to include cooler skin temperatures and negative capillary refill.